Early apoptosis in different models of cardiac hypertrophy induced by high renin-angiotensin system activity involves CaMKII - Velez Rueda, Jorge Omar (2012)
The objective of this study was to establish whether 1) hyperactivity of renin-angiotensin-aldosterone system (RAAS) produces apoptosis in early stages of cardiac disease; and 2) Ca2+-calmodulin-dependent protein kinase II (CaMKII) is involved in these apoptotic events. Two models of hypertrophy were used at an early stage of cardiac disease: spontaneously hypertensive rats (SHR) and isoproterenol-treated rats (Iso-rats). At 4 mo, SHR showed blood pressure, aldosterone serum levels, used as RAAS activity index, and left ventricular mass index, used as hypertrophy index, above control values by 84.2 ± 2.6 mmHg, 211.2 ± 25.8%, and 8.6 ± 1.1 mg/mm, respectively. There was also an increase in apoptotis (Bax-to-Bcl-2 ratio and terminal deoxynucleotidyl transferase dUTP-mediated nick-end labeling positive cells) associated with an enhancement of CaMKII activity with respect to age-matched controls (phosphorylated-CaMKII, 98.7 ± 14.1 above control). Similar results were observed in 4-mo-old Isorats. Cardiac function studied by echocardiography remained unaltered in all groups. Enalapril treatment significantly prevented hypertrophy, apoptosis, and CaMKII activity. Moreover, intracellular Ca2+ handling in isolated myocytes was similar between SHR, Iso-rats, and their aged-matched controls. However, SHR and Iso-rats showed a significant increase in superoxide anion generation (lucigenin) and lipid peroxidation (thiobarbituric acid reactive substance). In transgenic mice with targeted cardiomyocyte expression of a CaMKII inhibitory peptide (AC3-I) or a scrambled control peptide (AC3-C), Iso treatment increased thiobarbituric acid reactive substance in both strains, whereas it increased CaMKII activity and apoptosis only in AC3-C mice. Endogenous increases in RAAS activity induce ROS and CaMKII-dependent apoptosis in vivo. CaMKII activation could not be associated with intracellular Ca2+ increments and was directly related to the increase in oxidative stress. © 2012 by the American Physiological Society.